The Effect of Efficiency and Credit Risk on Islamic Banking Stability in The Gulf Cooperation Council Countries - Qurba, Ulul; Juliana Jaya, Tiara (Journal of Finance and Islamic Banking, 2023)
Previous studies on the effect of efficiency on the stability of Islamic banking have not extensively explored the potential influence of credit risk on stability. Additionally, inconsistencies in previous study results and contradictions with existing theories exist. This study aims to examine the impact of Efficiency and Credit Risk on Islamic banking stability in GCC member countries. Stability is measured using the Z-Score, Efficiency is assessed through the DEA method, and Credit Risk is determined by the NPF ratio. The study employs a purposive sampling method, with data collected from 9 Islamic banks in GCC member countries and analyzed using Panel Data Regression analysis in Eviews 12.0. Results indicate that efficiency has an insignificant effect on Islamic banking stability, while credit risk shows a positive yet insignificant influence on stability. However, both independent variables simultaneously affect Islamic banking stability. This study contributes to understanding the levels of stability, efficiency, and credit risk in Islamic banking within GCC countries, known for hosting some of the world's top Islamic banks, and sheds light on the impact of efficiency and credit risk on bank stability.